Formation of β-cyclodextrin inclusion complexes with a series of structurally related parabens: Preparation, physicochemical characterization and antifungal properties - Wenwen Zhang; Tai-Ping Zhou; Wenjing Zou; Yuyu Wang; Kexuan Wang; Yichao Yang; Chuan Liu; Zhuochao Tu; Qingqing Liu; Yongjun Yuan (Carbohydrate Polymer Technologies and Applications, 2025)
In β-cyclodextrin (β-CD) complexation, the structure of the guest compound critically influences the physicochemical properties and bioactivities of the resulting materials. This study investigated the complexation of β-CD with a series of structurally related parabens and explored their structure, physicochemical properties, and antifungal activity. The result showed that increasing the amount of guest compound during preparation led to higher loading efficiency (LE) but lower encapsulation efficiency (EE). A 1:1 stoichiometry between parabens and β-CD was confirmed, with the stability constant positively correlated with enhanced paraben solubility. Density functional theory calculations suggest the inclusion complex as a ‘Model A’ configuration, in which the benzene ring of paraben resides deeply within the β-CD cavity while the -OH group is positioned near the narrower rim of the β-CD torus. Additionally, the formation of the inclusion complex was further validated by scanning electron microscopy, differential scanning calorimetry, thermogravimetric analysis, X-ray diffraction, Fourier transform infrared spectroscopy, and 1H nuclear magnetic resonance. These analyses also reveal distinct physicochemical properties and new solid crystalline phases of the inclusion complex. All the β-CD/parabens inclusion complexes maintained antifungal activity against Aspergillus niger, and the parabens with longer alkyl chains achieved superior antifungal results. BP-IC, PP-IC, and IBP-IC exhibited MIC values of 1.25, 5, and 10 mg/mL, respectively, while the other inclusion complexes showed MICs over 10 mg/mL.